Antipodal Shakespeare : remembering and forgetting in Britain, Australia and New Zealand, 1916-2016 /: remembering and forgetting in Britain, Australia and New Zealand, 1916-2016. (2018) - McMullan, Gordon, 1962-; Mead, Philip, 1953-; Ferguson, Ailsa Grant; Flaherty, Kate (Kathryn J.); Houlahan, Mark, 1960-
No abstract available